Infrahumanization and Dehumanization of Women in Turkish Comedy Films as an Element of Comedy - Mert, Melek Kaymaz; Turedi, Humeyra (Univ Pittsburgh, Univ Library System, 2025)
This article's goal is to use the ideas of infrahumanization and dehumanization to describe how women are portrayed in Turkish comedies. Dehumanization is the process of describing a person with animalistic or robotic traits. Like dehumanization, infrahumanization is the belief that one's own group has more complex emotions than others, while members of the other group merely have animal-like innate feelings. Turkish women were portrayed as less human in this context, and this study explores whether this impression exists. The narrative analysis method was used to study popular comedy films shot between 1970 and 1979 to arrive at the answer to the query. Twenty Turkish comedy films were analyzed, and it was shown that both dehumanization and infrahumanization occurred.
Keywords: Film; Comedy; Woman; Infrahumanization; Dehumanization